ANALISIS DESAIN INTERIOR KANTOR CALL CENTER TELKOMSEL DI GEDUNG INFOMEDIA NUSANTARA, BANDUNG DENGAN PENDEKATAN PSIKOLOGI RUANG - Shafira Andriani; Djoko Murdowo; Rangga Firmansyah (Ide dan Dialog Desain Indonesia (Idealog), 2018)
Telkomsel Call Center Office is the call center service office for 24 hours which is facilitated by the telecommunications operator service companies Telkomsel in order to optimize the quality of service to its customers. Service optimisation is certainly influenced by internal company both in terms of the work system as well as where its taken place. One case study is taken, i.e. Telkomsel Call Center Office in Gedung Infomedia Nusantara -Bandung. Interior design on this Office has not applied optimally where affect the satisfaction of workers, mainly call center agents. This often raises the boredom on the agents whom do their work repeatedly to serve the consumers who don't rarely give them complaints or criticism. Using a research method of qualitative descriptive (comparative analysis of the condition in existing interior design with the theory of psychological space (five aspects which can form a good workplace design)), it is evident that Telkomsel Call Center Office interior design is not applied optimally to support satisfaction of workers in order to optimize its performance.